Extraction of Gambier using the boiling method and antibacterial activity test - Uyun, Hendri Satria Kamal; Putra, Panji Marvin; Suhardana, Gian; Bellatasie, Rezlie; Wiliantari, Selvia; Fajrina, Anzharni; Ramadhani, Putri (Riset Informasi Kesehatan, 2025)
Gambier is a dry extract derived from the Uncaria gambir (Hunter) Roxb plant. In this study, gambier extraction was carried out by boiling. The obtained Gambier extract is then tested for quality according to SNI 01-3391-1994. From the quality test results, it was concluded that the Gambier produced met quality 1. The gambir extract was tested for its antibacterial activity against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Antibacterial tests against S. aureus and E. coli, with concentrations of 10%, 15%, and 20%, show strong inhibition activity. While the antibacterial test against P. aeruginosa at a concentration of 10% has moderate inhibition, at concentrations of 15% and 20% has strong inhibition. Gambier has good antibacterial activity and potential to be developed into a natural ingredient product with potential as an antibacterial.